Treatment of metastatic hepatocellular carcinoma with lenvatinib. Case report and literature review - Konstantin V. Menshikov (IP Habib O.N., 2021)
Hepatocellular carcinoma (HCC) or liver cancer is the most common primary malignant tumor of the liver, which is characterized on the first place by a poor prognosis. HCC was diagnosed in 92 patients (62.6%) in 2019 and the period from January to April 2020 in the Republic of Bashkortostan, and among them, 68.47% had stage IV cancer. International professional guidelines suggest screening for early HCC detection. Systemic drug therapy is the treatment of choice for inoperable HCC according to professional guidelines. Inhibition of the VEGF pathway is one of the current methods of therapy for advanced HCC. Lenvatinib is a tyrosine kinase inhibitor for the treatment of advanced HCC that is not subject to local interventions. This article provides a description of a clinical case of successful treatment of a 67-year-old patient with advanced hepatocellular carcinoma. He was appointed for targeted therapy with lenvatinib for HCC that was not subject to local interventions, which led to long-term stabilization. There was a positive trend in the patients condition from the first weeks of therapy. The working capacity was restored. The therapy showed a satisfactory tolerability profile.